O trabalho do enfermeiro na atenção básica de Belo Horizonte: avaliação das ações programáticas - Camila Mendes dos Passos (2011)
The study is a byproduct of the study "Evaluation of Primary Health Care in Belo Horizonte, use, supply and accessibility of services", funded by FAPEMIG (PIRES; GOTTEMS, 2009). From the discussion of the results of this research aimed to evaluate the work of nurses in primary care from Belo Horizonte in relation to consultation in the nursing program actions of the Family Health Program. We evaluated their work in an action program for every area that comprises four basic clinics: internal medicine, pediatrics, gynecology and obstetrics. This is an evaluation study, descriptive and exploratory performed in 10 basic health units (BHU) in Belo Horizonte. The study consists of two complementary steps. The first stage of the construction of two logic models for each program action addressed. The data source was used in official documents of the Municipal Health Secretariat of Belo Horizonte. In the second analyzed the use, supply and organization of nursing consultation on programmatic actions. The source of information on the use and analysis of the organization was the database of the study "Evaluation of Primary Care in Belo Horizonte, use, supply and accessibility of services (PIRES; GOTTEMS, 2009). Data on the offering were originated by the Health Information System in the city of Belo Horizonte. We calculated the descriptive statistics for quantitative data and thematic analysis for qualitative data. The results showed that nurses have responsibilities related to educational, clinical, and planning and organization, but with limited descriptions of the detailed prescription drugs or over the test requests.The health problems that led the user to use the services focused on three groups, which are mild acute conditions, return visits and programmatic actions / control of diseases. The attendance of the nurse, described as the nursing consultation was one of the visits less frequently used. For those attending the service with issues of programmatic actions / control of diseases, their use was even lower. There was also a scarcity of nursing consultations, particularly in programmatic actions. It was found that the units have a stake homogeneous but irregular, nurses through individual consultation in the programs analyzed. The nurse organizes its work showing a decline of classical actions of public health - the nursing consultation in health programs. It was concluded that although the Family Health Program is widely deployed in the city, the nurses' work falls short of what is referred to in official documents.